2017
DOI: 10.1016/j.ncl.2017.01.008
|View full text |Cite
|
Sign up to set email alerts
|

Frontotemporal Dementia

Abstract: Frontotemporal Dementia (FTD) is a heterogeneous disorder with distinct clinical phenotypes associated with multiple neuropathologic entities. Presently, the term FTD encompasses clinical disorders that include changes in behavior, language, executive control and often motor symptoms. The core FTD spectrum disorders include: behavioral variant FTD (bvFTD), nonfluent/agrammatic variant primary progressive aphasia (nfvPPA), and semantic variant PPA (svPPA). Related FTD disorders include frontotemporal dementia w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
323
0
28

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 334 publications
(352 citation statements)
references
References 243 publications
(290 reference statements)
1
323
0
28
Order By: Relevance
“…Frontotemporal dementia (FTD), the leading cause of dementia in middle age, comprises a heterogeneous group of neurodegenerative conditions characterized by diverse cognitive and behavioral manifestations (Olney et al, 2017). Familial forms of the disease are often caused by mutations of the progranulin, tau, or C9orf72 gene, but sporadic forms are more common (Olney et al, 2017).…”
Section: The Nvu In Neurodegenerative Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…Frontotemporal dementia (FTD), the leading cause of dementia in middle age, comprises a heterogeneous group of neurodegenerative conditions characterized by diverse cognitive and behavioral manifestations (Olney et al, 2017). Familial forms of the disease are often caused by mutations of the progranulin, tau, or C9orf72 gene, but sporadic forms are more common (Olney et al, 2017).…”
Section: The Nvu In Neurodegenerative Diseasementioning
confidence: 99%
“…Familial forms of the disease are often caused by mutations of the progranulin, tau, or C9orf72 gene, but sporadic forms are more common (Olney et al, 2017). Resting CBF is reduced in the frontal, parietal and temporal cortex of presymptomatic patients, an effect independent of atrophy (Dopper et al, 2016).…”
Section: The Nvu In Neurodegenerative Diseasementioning
confidence: 99%
“…Tauopathies are subclassified as either primary or secondary, depending on the degree to which tau pathology occurs independently of other proteopathies (e.g., Aβ, α-syn, TDP-43). FTLD is a collection of non-AD neurodegenerative disorders affecting primarily the frontal and temporal lobes (157). FTLD can be further divided into three histological subtypes based upon the predominant proteopathy: FTLD-tau, FTLD-TDP, and FTLD-FUS (158).…”
Section: Non-ad Tauopathiesmentioning
confidence: 99%
“…Frontotemporal dementia (FTD) used to be an umbrella term for clinical syndromes comprising progressive behavioral disturbances and language deficits due to focal neurodegeneration in parts of the frontal and temporal lobes (FTLD). Current classifications differentiate the behavioral variant of frontotemporal dementia (bvFTD) and three subtypes of primary progressive aphasia (PPA) specified as agrammatic variant (avPPA), semantic variant (svPPA) and logopenic variant (lvPPA) (Figure ) . The underlying histopathology is variable and includes different forms of tauopathies, TDP43‐proteinopathies and atypical Alzheimer dementia (AD) pathology – the latter being associated with lvPPA (“atypical AD”).…”
Section: Introductionmentioning
confidence: 99%
“…Clinical neuropsychological testing is the diagnostic key for bvFTD and PPA types, whereas neuroimaging is mainly used to rule out differential diagnoses and comorbidities. [3][4][5] A majority of MRI studies dealing with differential diagnoses of these dementia forms focused on focal atrophy analyzing volumetric data or morphometric patterns. 6,7 More recent studies showed alterations in functional connectivity with diffusion tensor imaging (DTI) and in brain activity with arterial spin labeling (ASL) or with BOLD imaging.…”
Section: Introductionmentioning
confidence: 99%